Energy Levels and Electromagnetic Transition of 90-94mo Nuclei Using Ibm-1 - Omar Ahmed Muaffaq; Ahmed A. Al-Rubaiee (University of Thi-Qar Journal of Science, 2020)
The energy states for the  J , b ,  ɤ  bands and electromagnetic transitions B (E2) values for even – even molybdenum 90 – 94 Mo nuclei are calculated in the  present work of "the interacting boson model (IBM-1)" . The parameters of the equation of IBM-1 Hamiltonian are determined which yield the best excellent suit the experimental energy states . The positive parity of energy states are obtained by using  IBS1. for   program for even 90 – 94 Mo isotopes with bosons number 5 , 4 and 5 respectively. The" reduced transition probability B(E2)" of these neuclei are calculated and compared  with the  experimental data . The ratio of the excitation energies of the  41+ to 21+ states ( R4/2) are also calculated . The calculated and experimental (R4/2) values showed that the 90 – 94 Mo nuclei have the vibrational dynamical symmetry U(5). Good agreement was found from comparison between  the calculated energy states and electric quadruple probabilities B(E2) transition of the 90–94Mo isotopes with the experimental data .